Clean Living Culture through Online Learning Using Digital Media for Junior High School Students - Desi Arita Maryani Br. Sinaga; Asep Bayu Dani Nandiyanto (International Journal of Research and Applied Technology (INJURATECH), 2022)
The purpose of this study was to analyse the teaching of clean and healthy living culture in daily life through online learning using digital media. This learning uses Zoom meetings, google forms and the Wordwall site and provides pretest and posttest before and after learning to 22 junior high school students in Dayun District. Learning begins by introducing a clean and healthy living culture and the use of digital media such as Zoom meetings, Google forms and the Wordwall site. Pretest and Posttest are given through Google Forms with 20 questions. The results of the pretest and posttest given, show on average that students can know well the culture of clean and healthy living in daily life by using digital media as much as 81.82 points, but in using digital media as a tool for learning for students less can be said. This is due to various obstacles faced by students including, students rarely interact with teachers via zoom and only give homework through Google Classroom and WhatsApp, there are network problems or signals that occur when online learning takes place and lack of knowledge of digital media used such as laptop or cell phone. In this case, the introduction to sites such as Wordwall is also very minimal, so it requires a lot of interaction in using the site. This research can provide new information about learning the culture of clean and healthy living through online learning using digital media and shows the obstacles in using it